Analisis Penerapan Prinsip bagi Hasil Penjualan Ikan Tambak dalam Perspektif Ekonomi Islam (Studi Kasus Nagari Padang Gelugur Kabupaten Pasaman) - Fitri Syahdini; Rahmi Rahmi (Lembaga Yasin AlSys, 2026)
Although the application of profit-sharing principles in fish pond businesses has received attention in several previous studies, research that specifically discusses the discrepancy between initial agreements and actual practices from the perspective of Islamic economics remains limited. This study aims to analyze the application of profit-sharing principles in the sale of pond fish and to evaluate its conformity with the perspective of Islamic economics in Nagari Padang Gelugur, Pasaman Regency. This study used a qualitative approach with a case study design, involving 10 participants consisting of 7 fish pond managers, 2 fish pond owners, and 1 middleman selected using purposive sampling. Data were collected through interviews, observation, and documentation, then analyzed using interactive thematic analysis techniques. The results showed a discrepancy between the initial profit-sharing agreement of 30%:70% and the actual practice in the field, which changed to 50%:50%. The cooperation was also carried out verbally without a written agreement, thereby potentially creating ambiguity in the contract. In addition, the risk of loss was borne more by the fish pond owners, indicating an imbalance in risk distribution. These findings contribute to the development of Islamic economics studies, particularly in relation to the concept of mudharabah and justice in muamalah, and expand understanding of profit-sharing practices in the fish pond sector. The conclusion of this study emphasizes the importance of contractual clarity, consistency in implementing agreements, and balance in risk distribution in profit-sharing cooperation. Its practical implication is that fish pond business actors and local governments need to encourage the application of sharia principles through contracts that are clearer, written, and just.